2020
DOI: 10.1167/tvst.9.5.24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Morphology of the Foveal Pit Between African and Caucasian Populations

Abstract: The purpose of this study was to characterize foveal pit morphology in an African (Ghanaian) population, to compare it to that of a Caucasian group and to determine if it varied with age in the two populations. Methods: The depth, diameter, slope, and volume of the foveal pit were interpolated from optical coherence tomography volume scans recorded in 84 Ghanaian and 37 Caucasian individuals. Their association with age, sex, and ethnicity was investigated using multilevel regression models. Results: The foveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…On one end of the pigmentation spectrum are Black individuals, who have deeper and broader foveal pits. 12,13 On the other end are patients with albinism, who range from having an absent foveal pit to a shallow pit. 11 White individuals and individuals from other racial backgrounds fall in between these extremes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one end of the pigmentation spectrum are Black individuals, who have deeper and broader foveal pits. 12,13 On the other end are patients with albinism, who range from having an absent foveal pit to a shallow pit. 11 White individuals and individuals from other racial backgrounds fall in between these extremes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Black individuals have significantly deeper and broader pits compared to their White counterparts. 12,13 While there is no evidence for racial differences in retinal pigment epithelium melanin, there are racial differences in choroidal melanin. 14 If racial differences in choroidal melanin result in differences in foveal morphology, it stands to reason that individual variation in choroidal melanin could contribute to the above mentioned variation in foveal morphology.…”
mentioning
confidence: 99%
“…This is not the only issue that arises when using FAZ-based metrics. Within normal eyes, the size of the FAZ is highly variable, influenced by patient age, sex, race, central foveal thickness, and axial length [104][105][106][107][108][109]. Foremost among these factors is axial length, a measure of the length of the eyeball from the corneal surface to the retinal pigment epithelium.…”
Section: Faz Area and Faz-related Measurementsmentioning
confidence: 99%
“…The main objective of this approach is to study the fovea as a whole by computing a set of parameters that describe foveal pit features such as slope, width or depth. Applying this analysis, studies in healthy populations discovered important racial and sex differences in foveal pit morphology [19][20][21][22]. Additionally, some studies investigated differences in the fovea of patients with Parkinson's disease [23][24][25], foveal retinopathy [26] and neuromyelitis optica spectrum disorders [27].…”
Section: Introductionmentioning
confidence: 99%
“…An accurate placement of the foveal center is therefore crucial. However, not all studies included a step to locate the foveal center [20], and there has not been much research into comparing different foveal center location approaches. Common strategies include using the built-in function of Cirrus scanner [19,25], and using the minimum thickness point of either the TRT map [22,28], or each B-scan [29,30].…”
Section: Introductionmentioning
confidence: 99%